Control interno y su incidencia en la productividad de la empresa “Automotriz Mamonte’’ cantón Quevedo, año 2022. - Mamonte Rizo, Dayanna Mishell (2024)
The present research project “Internal control and its impact on the productivity of the Automotive Company “Mamonte” canton Quevedo, year 2022”, focused on the crucial relationship between internal control and productivity in the automotive industry. In a highly competitive market, efficiency and effective resource management are essential to the success of automotive companies. The objective was to evaluate the impact of internal control on the productivity of the “Mamonte” Automotive Company. Deductive, inductive, analysis and synthesis methods were applied. Questionnaires were developed to examine internal control practices, such as process monitoring, risk management and internal audit; thus demonstrating how these practices directly impact the productivity of the “Mamonte” Automotive Company. Acceptable audit risks were determined. The confidence level obtained a percentage of 76%, the Control Risk 24%, the Inherent Risk with a percentage of 46% and the Detection Risk with a percentage of 6%. The findings underline that the current situation of operational processes significantly influences the planning of future strategies.